Menciptakan Rasa Peduli dan Kesadaran Lingkungan melalui Gerakan Bersih Bersama Mahasiswa dan Masyarakat di Kampus - Sarwo Waskito; Achmad Bahrul Jawahir; Rommy Hardyansah; Rio Saputra; Didit Darmawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The clean-up movement, involving students and the campus community, is a crucial effort to foster environmental awareness and concern at Sunan Giri University, Surabaya. The program utilizes the Participatory Action Research (PAR) method, ensuring direct involvement of all participants, from identifying problems and planning activities to implementing the clean-up, to conducting joint evaluations. The problems encountered in the field were quite diverse, including accumulated trash, unmanaged weeds, clogged drains, and a lack of understanding of proper waste management. Activities included campus cleaning, waste sorting, weed removal, landscaping and green space development, and providing education on the importance of environmental protection. Results demonstrated increased participant awareness and behavioral changes toward more environmentally responsible behavior. In addition to creating a cleaner and more organized campus, the program also strengthened collaboration between students and the community as a form of ongoing service. Therefore, this clean-up movement has proven effective in fostering empowerment and building a culture of environmental awareness within the university.